DEVELOPMENT OF SOFT SKILLS IN FUTURE CONSTRUCTION INDUSTRY PROFESSIONALS (Innovative professional education, 2025)
The importance of developing soft skills among future specialists in the construction industry is discussed in the context of Ukraine’s reconstruction. International experience of rebuilding countries after the destruction caused by military actions is analyzed. The ways of integrating soft skills development into vocational (vocational-technical) education are proposed, which will contribute to training specialists capable not only of rebuilding the country but also of making it more modern and resilient to future challenges
Keywords: skills, construction industry, vocational education, crisis management, adaptability